Novel Cardiolipins from Uncultured Methane-Metabolizing Archaea. (14th May 2012) - Yoshinaga, Marcos Y.; Wörmer, Lars; Elvert, Marcus; Hinrichs, Kai-Uwe
Abstract : Novel cardiolipins from Archaea were detected by screening the intact polar lipid (IPL) composition of microbial communities associated with methane seepage in deep-sea sediments from the Pakistan margin by high-performance liquid chromatography electrospray ionization mass spectrometry. A series of tentatively identified cardiolipin analogues (dimeric phospholipids or bisphosphatidylglycerol, BPG) represented 0.5% to 5% of total archaeal IPLs. These molecules are similar to the recently described cardiolipin analogues with four phytanyl chains from extreme halophilic archaea. It is worth noting that cardiolipin analogues from the seep archaeal communities are composed of four isoprenoidal chains, which may contain differences in chain length (20 and 25 carbon atoms) and degrees of unsaturation and the presence of a hydroxyl group. Two novel diether lipids, structurally related to the BPGs, are described and interpreted as degradation products of archaeal cardiolipin analogues. Since archaeal communities in seep sediments are dominated by anaerobic methanotrophs, our observations have implications for characterizing structural components of archaeal membranes, in which BPGs are presumed to contribute to modulation of cell permeability properties. Whether BPGs facilitate interspecies interaction in syntrophic methanotrophic consortia remains to be tested.